2021
DOI: 10.1158/1078-0432.ccr-21-0585
|View full text |Cite|
|
Sign up to set email alerts
|

Pilot Phase II Trial of Neoadjuvant Immunotherapy in Locoregionally Advanced, Resectable Cutaneous Squamous Cell Carcinoma of the Head and Neck

Abstract: Purpose: In locoregionally advanced, resectable cutaneous squamous cell carcinoma of the head and neck (CSCC-HN), surgery followed by radiotherapy is standard but can be cosmetically and functionally devastating, and many patients will have recurrence. Patients and Methods: Newly diagnosed or recurrent stage III–IVA CSCC-HN patients amenable to curative-intent surgery received two cycles of neoadjuvant PD-1 inhibition. The pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 33 publications
1
74
1
2
Order By: Relevance
“…Immunotherapy has the ability to gain rapid oncological responses as was highlighted by Ferrarotto et al in their neoadjuvant study where 70% of patients (14/20) achieved a complete or major pathological response post two cycles of cemiplimab 350 mg/3-weekly ( 17 ). Rapid clinical response is of particular importance for patients who have symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunotherapy has the ability to gain rapid oncological responses as was highlighted by Ferrarotto et al in their neoadjuvant study where 70% of patients (14/20) achieved a complete or major pathological response post two cycles of cemiplimab 350 mg/3-weekly ( 17 ). Rapid clinical response is of particular importance for patients who have symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The only published neoadjuvant cemiplimab study utilizing cemiplimab 350 mg/3-weekly with a response assessment post two cycles followed by surgery demonstrated a remarkable 70% major pathological response rate with 55% of patients achieving a complete pathological response ( 17 ). All patients in this study received curative surgery as part of the study design; however, these impressive results raise the pertinent question of whether less extensive surgery is feasible following immunotherapy, a potential area of investigation for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, neoadjuvant studies allow for earlier assessment, using pathologic response, compared to adjuvant studies, where survival data can take many years to mature. A pilot phase II study of two doses of neoadjuvant cemiplimab for patients with locally advanced, curable CSCC resulted in 14/20 patients (70%; 95% CI 45.7–88.1) with a pathological complete response ( n = 11) or major pathological response ( n = 3) [ 160 ]; this was despite only 30% (95% CI 11.9–54.3) showing a partial response by RECIST, highlighting the challenges of assessing ICI response using current radiological criteria. Neoadjuvant studies of other ICIs, as well as combination neoadjuvant treatment with dual anti-PD(L)1 with anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) blockade, are ongoing [NCT04154943] [ 161 , 162 ].…”
Section: Treatment Advancesmentioning
confidence: 99%
“…Finally, the use of systemic immunotherapy in an attempt to reduce tumoral burden, thereby allowing for a less extensive surgery (neoadjuvant therapy), is being assessed in ongoing clinical trials on advanced cSCC. A recently published phase II pilot trial of neoadjuvant immunotherapy with cemiplimab has shown pathologically complete responses in 70% of the patients [40]. Although these results were obtained from patients with advanced but resectable tumors, it can be hypothesized that the same neoadjuvant approach can be applied to borderline resectable or even unresectable advanced cSCC in the future.…”
Section: Surgery For Patients With Advanced Csccmentioning
confidence: 99%